STUDY ON STRUCTURE AND CRYSTALLIZATION OF POLYPROPYLENE GRAFTED MALEIC ANHYDRIDE/NANOCLAY COMPOSITE - Bui Chuong; Dang Viet Hung (ASEAN Journal on Science and Technology for Development, 2008)
Nanocomposite from polypropylene grafted maleic anhydride (PP-g-MA) and nanoclay were prepared by melt proccessing in Brabender extruder. XRD analysis shows the formation of nanostructure (intercalated and exfoliated) of nanocomposite with interlayer space (d-space) increasing from 26.3Å to 30.9Å. These structures, however, do not affect the microcrystalline structure of polymer part of nanocomposite in whole. The study on nonisothermal crystallization shows the development in 3-dimentional direction of crystallites, that means spherulite form of crystalline structure.